Hexadic model of knowledge existence cycle - Budrevičius, Algirdas (Information & Media, 1994)
The article deals with problems of knowledge engineering. Knowledge is analysed as phenomenon having certain duration in time. The main phases of knowledge existence cycle are singled out and thoroughly analysed. Mathematical models of knowledge existence cycle and its phases as well as their curves are presented and explained.